2006
DOI: 10.1159/000094363
|View full text |Cite
|
Sign up to set email alerts
|

Propionyl-<i>L</i>-Carnitine Therapy: Effects on Endothelin-1 and Homocysteine Levels in Patients with Peripheral Arterial Disease and End-Stage Renal Disease

Abstract: Background/Aims: Recent data have addressed the issue of higher levels of homocysteine (Hcy) and endothelin-1 (ET-1) in end-stage renal disease (ESRD) that may be considered an independent predictor for cardiovascular disease. The prevalence of peripheral arterial disease (PAD) in patients with ESRD has been reported to be relevant, highlighting its clinical importance. We aimed to explore the therapeutic role of propionyl-L-carnitine (PLC) in hemodialysis patients with PAD by measuring ankle/brachial index (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that oxidative stress is associated with PAD in hemodialysis patients. Reducing oxidative stress in these patients with propionyl L-carnitine can significantly increase nitric oxide formation, decrease vasoconstrictive endothelin-1 production, and improve vascular hemodynamic flow 46, 47 . Together, these findings suggest that the association between L5% and lower-extremity PAD in uremia patients may in part be attributed to the promotion of oxidative stress by L5 LDL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that oxidative stress is associated with PAD in hemodialysis patients. Reducing oxidative stress in these patients with propionyl L-carnitine can significantly increase nitric oxide formation, decrease vasoconstrictive endothelin-1 production, and improve vascular hemodynamic flow 46, 47 . Together, these findings suggest that the association between L5% and lower-extremity PAD in uremia patients may in part be attributed to the promotion of oxidative stress by L5 LDL.…”
Section: Discussionmentioning
confidence: 99%
“…78,89,90 These contradictory findings might be explained by differences in study design, since trials that showed enhanced blood flow included higher doses of PLC. More recent trials also identified a reduction in oxidative stress markers 78,91,92 and an enhanced bioavailability of NO 78,92 in PAD patients treated with PLC. In particular, a recent outstanding study by Stasi et al 93 showed that PLC injection accelerates rabbit hind-limb post-ischemic blood flow recovery and the restoration of vascular function by sustaining positive dilative arteriogenetic remodeling and by reducing oxidative-stress-induced impaired endothelial function.…”
Section: Plc and Peripheral Arterial Diseasementioning
confidence: 93%
“…These contradictory findings might be explained by differences in study design, since trials that showed enhanced blood flow included higher doses of PLC. More recent trials also identified a reduction in oxidative stress markers 78,91,92 and an enhanced bioavailability of NO 78,92 in PAD patients treated with PLC. In particular, a recent outstanding study by Stasi et al 93 .…”
Section: Clinical Evidence Of the Therapeutic Value Of Plcmentioning
confidence: 93%
“…In recent years, PLC has shown therapeutic benefits in the management of disease such as peripheral vascular disease, myocardial ischemia, congestive heart failure, and erectile dysfunction ( Table 2) [68][69][70][71][72][73][74][75][76][77][78][79].…”
Section: Clinical Indication Of Propionyl-l-carnitinementioning
confidence: 99%